Utilizing a private collection to explain the variation present in turn of the century wrenches, spark plugs, and corn huskers - Johnson, Mitchell La Verne Hintzman (My University, 2012)
This study focuses on three broad categories of a turn of the century farming collection containing more than 40,000 total items. The three categories examined in this study include: wrenches, spark plugs, and corn huskers. Within each category, judgmental samples were selected to reflect the variation present in the collection. Repeated interviews with the collection's owner, utilization of collector's guides, and historical documentation has yielded a comprehensive explanation of the enormous variation present in these artifacts. This variation is based upon a number of factors which includes: change over time, individual use, differing functions within an artifact type, and added variation in pursuit of a patent. Due to the increasing age of the majority of these collectors, such investigations should be an immediate concern before an entire generation of knowledge is essentially lost.